Qris Ritel Rescue: Penerapan Digitalisasi dalam Pengembangan Bisnis Ritel - Andry Nurmansyah; Erfian Ramdani Kuswara; Hasna Nabila Julita; Intan Nur'Aini; Nabila Rahmawati (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
This study aims to evaluate the impact and effectiveness of implementing the Quick Response Code Indonesian Standard (QRIS) payment system as a form of digitalization on the progress and sustainability of the retail business in the City of Bandung. The method applied in this study is descriptive with a quantitative approach. Data was obtained through the distribution of questionnaires to 30 respondents involved in retail businesses in the Cikutra and Cihaurgeulis Market areas using purposive sampling. The research findings indicate that the use of QRIS has a highly significant positive effect, where 100% of respondents experienced an increase in revenue and attracted the attention of younger customers. Additionally, the registration process and supporting facilities were rated as sufficient by 97% of respondents. However, results indicate that perceptions regarding the security of QRIS transactions still fall into the low category (50%), suggesting concerns about potential cybercrime. Overall, business owners demonstrated a high level of loyalty, with 100% intending to continue using QRIS over the long term.